2015
DOI: 10.1093/femsle/fnv197
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antimicrobial resistance and genetic diversity ofYersinia enterocoliticaisolated from retail frozen foods in China

Abstract: In this study, our aim was to estimate the extent of Yersinia enterocolitica contamination in frozen foods in China and determine the bioserotype, virulotype, antimicrobial resistance, and enterobacterial repetitive intergenic consensus-PCR (ERIC-PCR) genotyping profiles of recovered Y. enterocolitica isolates. Out of 455 samples collected between July 2011 and May 2014, 56 (12.3%) tested positive for Y. enterocolitica. The 70 isolated strains were grouped into five clusters and one singleton based on their ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
4
16
1
Order By: Relevance
“…Some studies have revealed that it can also survive and reproduce in vacuum packaging and refrigerated foods. [12][13][14][15] Food-based Yersiniosis epidemics are linked with multiple food items, including dairy, 13 meat, 16,17 poultry, fruits, vegetables, stewed and fermented products and also seafoods, 18,19 as given in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have revealed that it can also survive and reproduce in vacuum packaging and refrigerated foods. [12][13][14][15] Food-based Yersiniosis epidemics are linked with multiple food items, including dairy, 13 meat, 16,17 poultry, fruits, vegetables, stewed and fermented products and also seafoods, 18,19 as given in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…1,9 Regarding aminoglycosides, gentamicin, and streptomycin, low levels of resistance have been reported among Y. enterocolitica strains isolated in Iran, which is in accordance with reports from Italy (0%), China (4.3% to gentamicin and 8.6% to streptomycin), Austria (0%), Germany (0%), Turkey (0% to gentamicin and 4.8% to streptomycin), and Korea (0%). [25][26][27][28][29][30] The prevalence of resistance to other antibiotics used for the treatment of human yersiniosis (i.e., trimethoprim/sulfamethoxazole) was higher (17.1%) than those reported from Italy (0%) 25 and Malaysia, 31 but lower than that of China (74.3%). 26…”
Section: Discussionmentioning
confidence: 93%
“…[25][26][27][28][29][30] The prevalence of resistance to other antibiotics used for the treatment of human yersiniosis (i.e., trimethoprim/sulfamethoxazole) was higher (17.1%) than those reported from Italy (0%) 25 and Malaysia, 31 but lower than that of China (74.3%). 26…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations